Evaluasi Penggunaan Antibiotika Profilaksis Operasi Digestif Laparatomi - Selly Septi Fandinata; Eziah Ika Lubada; Ilil Maidatuz Zulfa (Journal Syifa Sciences and Clinical Research, 2022)
Laparotomy is a major operation and causes a lot of injuries, so the risk of infection of the laparotomy surgery wound is quite high. Surgical Site Infection (ILO) or Surgical Site Infection (ITP). Prevention of postoperative infection in patients with clean-contaminated surgery, and some clean operations with the use of prophylactic antibiotics. The purpose of this study was to evaluate the use of prophylactic antibiotics in patients with laparotomy surgery in a hospital in Surabaya. The research method is descriptive operational with retrospective data. The results of this study obtained as many as 160 patients aged 46-55 years at 20.6%, the sex of the respondents were dominated by male sex 66.3%, and the diagnosis of generalized peritonitis was 46.9%. The use of prophylactic antibiotics is class I cephalosporin antibiotics (cefazolin) with a dose of 1000-2000 mg, which is by the 2011 Ministry of Health guidelines.